Dinamika Post-Traumatic Stress pada Masyarakat Penyintas Bencana di Hunian Tetap Bumi Semeru Damai (BSD) - Ahmad Faisol; Bambang Subahri (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2026)
Natural disasters in the Semeru region have resulted not only in physical destruction but also in long-term psychological consequences for affected communities, particularly in the form of Post-Traumatic Stress (PTS). Although survivors have been relocated to permanent housing, traumatic stress often persists and fluctuates during the post-relocation phase. This study aims to explore the dynamics of Post-Traumatic Stress and the factors influencing its persistence among disaster survivors living in the Bumi Semeru Damai (BSD) permanent housing complex in Lumajang. This study employed a qualitative approach using a case study design and involved four disaster survivors with diverse ages and life backgrounds. Data were collected through in-depth interviews, direct observations, and documentation, and analyzed thematically using the Conservation of Resources (COR) theory. The findings indicate that Post-Traumatic Stress among survivors is dynamic and non-linear, with symptom intensity changing over time. The persistence of Post-Traumatic Stress (PTS) is strongly associated with the loss of critical resources, while social support functions as a protective factor that facilitates psychological adaptation. These findings highlight the need for post-disaster recovery strategies that prioritize long-term psychosocial support and resource strengthening.